The Needle in the Haystack : What Drives Labor and Product Market Reforms in Advanced Countries? - Duval, Romain (IMF Working Papers; Working Paper, 2018)
The political economy literature has put forward a multitude of hypotheses regarding the drivers of structural reforms, but few, if any, empirically robust findings have emerged thus far. To make progress, we draw a parallel with model uncertainty in the growth literature and provide a new version of the Bayesian averaging of maximum likelihood estimates (BAMLE) technique tailored to binary logit models. Relying on a new database of major past labor and product market reforms in advanced countries, we test a large set of variables for robust correlation with reform in each area. We find widespread support for the crisis-induces-reform hypothesis. Outside pressure increases the likelihood of reform in certain areas: reforms are more likely when other countries also undertake them and when there is formal pressure to implement them. Other robust correlates are more specific to certain areas-for example, international pressure and political factors are most relevant for product market and job protection reforms, respectively.